A Comparative Study between The Marketing Concepts of Chain-Hotels and Family Operated Hotels In India. - Bhandari, Nishit (2009)
In the age of globalization, India is one of the fastest growing economies of the world, successfully positioning itself as a major services provider. The hospitality industry of India is witnessing a boom and provides a vast range of tourism products for catering the needs of diverse sets of global and domestic customers. The purpose of this dissertation is to analyze the effectiveness and application of the core marketing concepts in the hotel industry. In Particular, concerned with the comparison between marketing of family operated and the chain hotel sectors of India.